Feed for ceramic die forming and forming method thereof

By increasing the adhesive content and forming process of ceramic spraying, the problems of poor spraying fluidity and difficulty in sintering in ceramic molding technology are solved, and complex parts are formed efficiently and production efficiency is improved, which is suitable for the production of high-end ceramic products.

CN119219414AInactive Publication Date: 2024-12-31SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411279788.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119219414A_ABST
    Figure CN119219414A_ABST
Patent Text Reader

Abstract

The invention discloses a feed for ceramic die forming and a forming method thereof. The mass ratio of ceramic powder to an adhesive in the feed is (1.5-2): (8.5-8), and the ceramic powder comprises the following components in percentage by mass: 92.5-96.5% of zirconium oxide, 3-6% of yttrium oxide and 0.1-1% of aluminum oxide; the binder comprises the following components in percentage by mass: 8-13% of high-density polyethylene, 4-7% of ethylene-vinyl acetate copolymer, 3-8% of stearic acid, 8-18% of paraffin and 60-70% of polyformaldehyde; the forming method mainly adopts warm mold pressing forming. The feed and the forming method thereof can solve the problems of poor fluidity, difficulty in forming complex parts, difficulty in sintering and the like of the ceramic feed in the existing mold pressing technology, and have the advantages of simple and efficient method, high forming quality, good product mechanical property, capability of forming complex parts and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of traditional ceramic powder metallurgy, in particular to a feed material for ceramic compression molding and a molding method thereof. Background Art

[0002] Ceramic compression molding is one of the commonly used ceramic green body forming processes in current production. It is to load the granulated ceramic powder into the mold, apply external force to squeeze the powder in the mold into shape, and finally sinter to form a ceramic block. Compression molding has the advantages of precise and controllable green body size, simple processing technology, and low cost. It is suitable for industrial continuous production of ceramic products with simple geometric shapes. However, since the powder used in this process contains less or no binder in the powder, the powder has poor fluidity, which can easily lead to density differences between the various parts of the pressed green body, uneven size shrinkage after sintering, and even crack defects in the product, which seriously reduces the yield of compression-molded ceramics and limits its application in high-end fields such as home bathroom, communication equipment, etc.

[0003] In view of the shortcomings of the above-mentioned compression molding, the existing technology uses injection molding process to form high-fluidity ceramic feed. It mainly injects ceramic powder mixed with a large amount of adhesive into a special mold at a certain temperature, and degreases and sinters to obtain the finished product. However, injection molding requires the use of a special injection machine and matching molds, which has low work efficiency, poor industrial interchangeability, high cost of special molds, and certain limitations on the scope of application.

[0004] In summary, in the existing technology, compression molding has the disadvantages of poor fluidity of ceramic feed, difficulty in forming complex parts and difficulty in sintering; and ceramic injection molding technology requires the use of a special injection machine and has low production efficiency. Facing the large demand for high-quality ceramic products in high-end fields such as home bathroom, communication equipment, etc., the industry urgently needs to solve the above problems and propose a feed for compression molding and its corresponding high-efficiency warm mold compression molding method. Summary of the invention

[0005] The main purpose of the present invention is to provide a feed material for ceramic compression molding and a forming method thereof in view of the deficiencies of the prior art, so as to solve the problems of poor fluidity of ceramic feed materials in the prior compression molding technology, difficulty in forming complex parts and difficulty in sintering.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A feed material for ceramic compression molding, comprising ceramic powder and a binder, wherein the mass ratio of the ceramic powder to the binder is (1.5-2):(8.5-8);

[0008] The ceramic powder includes the following components in percentage by mass:

[0009] Zirconia: 92.5-96.5%;

[0010] Yttrium oxide: 3-6%;

[0011] Alumina: 0.1-1%;

[0012] The adhesive comprises the following components in percentage by mass:

[0013] High-density polyethylene: 8-13%;

[0014] Ethylene-vinyl acetate copolymer: 4-7%;

[0015] Stearic acid: 3-8%;

[0016] Paraffin: 8-18%;

[0017] Polyoxymethylene: 60-70%.

[0018] Furthermore, the volume density of the ceramic powder is 1.3-1.4 g / ml.

[0019] Furthermore, the particle size D50 of the ceramic powder is 450 nm.

[0020] Furthermore, the feed material needs to be obtained through drying and mixing.

[0021] Furthermore, the drying mainly includes:

[0022] Heat the internal mixer to the set temperature, add the ceramic powder, slowly stir and dry. The drying temperature of the ceramic powder is 120±10℃, and the drying time is 10 to 20 minutes.

[0023] Furthermore, the feed material needs to be obtained through drying and banburying. The banburying mainly includes:

[0024] Add the mixed adhesive into an internal mixer and mix it with the ceramic powder. The temperature of the internal mixer is 170-200°C, the speed of the internal mixer is 5-30r / min, the total mixing time is 2-3h, and the mixture is stirred until it becomes dough-like. Lower the temperature of the internal mixer to 80-100°C, the speed of the internal mixer is 5-30r / min, and the mixing time is 10-30min to obtain a powdered feed for compression molding.

[0025] Furthermore, the powdered feed material for compression molding needs to be screened to obtain a powdered feed material D50 of 0.1 to 0.3 mm, and then compression molding is performed to obtain a green body.

[0026] Furthermore, the molding process parameters include:

[0027] Molding temperature: 120~180℃;

[0028] Molding pressure: 40~100MPa;

[0029] Molding insulation time: 5 to 20 minutes;

[0030] Furthermore, the compression molded green body is degreased to obtain a degreased green body, which is then sintered to obtain the ceramic product.

[0031] Furthermore, the degreasing adopts a nitric acid degreasing process, and the degreasing parameters include:

[0032] Nitric acid intake: 3-5 g / min;

[0033] Degreasing temperature: 110~130℃;

[0034] Degreasing time: 3-5h;

[0035] Furthermore, the sintering adopts a normal pressure sintering process, and the sintering parameters include:

[0036] Sintering temperature: 1400~1600℃;

[0037] Sintering holding time: 2~4h;

[0038] Sintering rate: 2~5℃ / min;

[0039] The present invention provides a feed material for ceramic compression molding, wherein the mass ratio of a binder to nano-ceramic powder is (1.5-2):(8.5-8), the ceramic powder comprises 92.5-96.5% by mass of zirconium oxide, 3-6% by mass of yttrium oxide, and 0.1-1% by mass of aluminum oxide; the binder comprises 8-13% by mass of high-density polyethylene, 4-7% by mass of ethylene-vinyl acetate copolymer, 3-8% by mass of stearic acid, 8-18% by mass of paraffin, and 60-70% by mass of polyoxymethylene.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. Compared with the conventional feed material for compression molding, the feed material provided by the present invention has a higher adhesive content, which helps to improve the fluidity of the feed material, so that the green body after compression has a more uniform density, a smoother surface, a higher yield rate, and good mechanical properties compared with the conventional compression molding.

[0042] 2. The warm mold pressing forming method adopted by the present invention does not require the use of a special injection molding machine. Compared with injection molding, it can form complex parts while reducing costs and greatly improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a SEM image of the green body fracture before catalytic degreasing of the feed in Example 1 of the present invention.

[0044] Figure 2This is a SEM image of the green body fracture after catalytic degreasing of the feed in Example 1 of the present invention.

[0045] Figure 3 This is a SEM image of the surface of the sintered body after sintering of the feed in Example 1 of the present invention. DETAILED DESCRIPTION

[0046] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.

[0047] In one embodiment, a feed material for ceramic compression molding includes ceramic powder and a binder, wherein the mass ratio of the ceramic powder to the binder is (1.5-2):(8.5-8);

[0048] The ceramic powder includes the following components in percentage by mass:

[0049] Zirconia: 92.5~96.5%

[0050] Yttrium oxide: 3-6%

[0051] Alumina: 0.1~1%

[0052] The adhesive comprises the following components in percentage by mass:

[0053] High-density polyethylene: 8-13%

[0054] Ethylene-vinyl acetate copolymer: 4-7%

[0055] Stearic acid: 3-8%

[0056] Paraffin: 8-18%

[0057] Polyoxymethylene: 60-70%

[0058] In a preferred embodiment, the volume density of the ceramic powder is 1.3-1.4 g / ml.

[0059] In a preferred embodiment, the particle size D50 of the ceramic powder is 400-500 nm.

[0060] In a preferred embodiment, the feed material is obtained by drying and mixing. The drying mainly includes:

[0061] Heat the internal mixer to the set temperature, add the ceramic powder, slowly stir and dry. The drying temperature of the ceramic powder is 120±10℃, and the drying time is 10 to 20 minutes.

[0062] In a preferred embodiment, the feed material is obtained by drying and mixing. The mixing mainly includes:

[0063] Add the mixed adhesive into an internal mixer and mix it with the ceramic powder. The temperature of the internal mixer is 170-200°C, the speed of the internal mixer is 5-30r / min, the total mixing time is 2-3h, and the mixture is stirred until it becomes dough-like. Lower the temperature of the internal mixer to 80-100°C, the speed of the internal mixer is 5-30r / min, and the mixing time is 10-30min to obtain a powdered feed for compression molding.

[0064] In a preferred embodiment, the powdered feed material for compression molding needs to be screened to obtain a powdered feed material D50 of 0.1 to 0.3 mm, followed by compression molding to obtain a green body.

[0065] The compression molding process parameters include:

[0066] Molding temperature: 120~180℃

[0067] Molding pressure: 40~100MPa

[0068] Molding insulation time: 5 to 20 minutes

[0069] In a preferred embodiment, the compression molded green body is degreased to obtain a degreased green body, which is then sintered to obtain the ceramic product.

[0070] The degreasing adopts nitric acid degreasing process, and the degreasing parameters include:

[0071] Nitric acid intake: 3-5 g / min

[0072] Degreasing temperature: 110~130℃

[0073] Degreasing time: 3-5h

[0074] The sintering adopts the atmospheric pressure sintering process, and the sintering parameters include:

[0075] Sintering temperature: 1400~1600℃

[0076] Sintering holding time: 2~4h

[0077] Sintering rate: 2~5℃ / min

[0078] Example 1

[0079] The feeding formula is:

[0080] High-density polyethylene: 0.18kg

[0081] Ethylene-vinyl acetate copolymer: 0.09kg

[0082] Stearic acid: 0.09kg

[0083] Paraffin: 0.27kg

[0084] Polyoxymethylene: 1.2kg

[0085] Ceramic powder: 9kg

[0086] The ceramic powder is selected according to the formula of the present invention, the same below.

[0087] Processing method:

[0088] 1. Heat the internal mixer to the set temperature of 120℃, add ceramic powder and slowly stir and dry for 15 minutes.

[0089] 2. Add the mixed adhesive into an internal mixer and mix it with the ceramic powder. The temperature of the internal mixer is 185°C, the speed of the internal mixer is 5-30 r / min, the total mixing time is 3 hours, and the mixture is stirred until it becomes dough-like. Lower the temperature of the internal mixer to 100°C, continue to stir the dough-like mixture formed in step 2, the speed of the internal mixer is 20 r / min, the mixing time is 20 minutes, and the mixture is crushed into powder to obtain a feed material for compression molding.

[0090] 3. The powdered feed material for compression molding obtained in step 2 is screened, and the obtained powdered feed material D50 is 0.1-0.3 mm. The molding process parameters include:

[0091] Molding temperature: 150℃

[0092] Molding pressure: 70MPa

[0093] Molding insulation time: 10min

[0094] according to Figure 1 It can be seen that before catalytic degreasing, the powder surface and gaps of the green body are covered with a large amount of flocculent adhesive, which makes the feed have good fluidity.

[0095] 4. Degrease the sample formed in step 4 with nitric acid to obtain a degreased blank. The nitric acid degreasing process parameters include:

[0096] Nitric acid intake: 4g / min

[0097] Degreasing temperature: 120℃

[0098] Degreasing time: 5h

[0099] according to Figure 2 It can be seen that after the green body is degreased with nitric acid, the POM is basically removed, and there are interconnected pores inside. The residual skeleton agent HDPE and the like form a network structure connecting the powders, and the shape of the green body is maintained.

[0100] 5. The sample after degreasing in step 4 is subjected to atmospheric pressure sintering to obtain the product. The atmospheric pressure sintering process parameters include:

[0101] Sintering temperature: 1500℃

[0102] Sintering holding time: 2h

[0103] Sintering rate: 5℃ / min

[0104] according to Figure 3 It can be seen that after degreasing and sintering, the grains of the molded green body are uniform, fine and tightly combined, no obvious holes are observed, and the grain boundaries are obvious.

[0105] Example 2

[0106] The feeding formula is:

[0107] High-density polyethylene: 0.19kg

[0108] Ethylene-vinyl acetate copolymer: 0.1kg

[0109] Stearic acid: 0.1kg

[0110] Paraffin: 0.3kg

[0111] Polyoxymethylene: 1.3kg

[0112] Ceramic powder: 8.7kg

[0113] The ceramic powder is selected according to the formula of the present invention, the same below.

[0114] Processing method:

[0115] 1. Heat the internal mixer to the set temperature of 120℃, add ceramic powder and slowly stir and dry for 10 minutes.

[0116] 2. Add the mixed adhesive into an internal mixer and mix it with the ceramic powder. The temperature of the internal mixer is 170°C, the speed of the internal mixer is 10 r / min, and the total mixing time is 2 h. Stir until it becomes a dough. Lower the temperature of the internal mixer to 85°C, continue to stir the dough-like mixture formed in step 2, the speed of the internal mixer is 20 r / min, the mixing time is 20 min, crush it into powder, and obtain the feed for compression molding.

[0117] 3. The powdered feed material for compression molding obtained in step 2 is screened, and the obtained powdered feed material D50 is 0.1-0.3 mm. The molding process parameters include:

[0118] Molding temperature: 150℃

[0119] Molding pressure: 70MPa

[0120] Molding insulation time: 10min

[0121] 4. Degrease the sample formed in step 4 with nitric acid to obtain a degreased blank. The nitric acid degreasing process parameters include:

[0122] Nitric acid intake: 4g / min

[0123] Degreasing temperature: 120℃

[0124] Degreasing time: 5h

[0125] 5. The sample after degreasing in step 4 is subjected to atmospheric pressure sintering to obtain the product. The atmospheric pressure sintering process parameters include:

[0126] Sintering temperature: 1500℃

[0127] Sintering holding time: 2h

[0128] Sintering rate: 5℃ / min

[0129] Example 3

[0130] The feeding formula is:

[0131] High-density polyethylene: 0.25kg

[0132] Ethylene-vinyl acetate copolymer: 0.15kg

[0133] Stearic acid: 0.15kg

[0134] Paraffin: 0.3kg

[0135] Polyoxymethylene: 1.25kg

[0136] Ceramic powder: 9kg

[0137] The ceramic powder is selected according to the formula of the present invention, the same below.

[0138] Processing method:

[0139] 1. Heat the internal mixer to the set temperature of 120℃, add ceramic powder and slowly stir and dry for 15 minutes.

[0140] 2. Add the mixed adhesive into an internal mixer and mix it with the ceramic powder. The temperature of the internal mixer is 200°C, the speed of the internal mixer is 20 r / min, and the total mixing time is 2 hours. Stir until it becomes a dough. Lower the temperature of the internal mixer to 80°C, continue to stir the dough-like mixture formed in step 2, the speed of the internal mixer is 15 r / min, the mixing time is 10 minutes, crush it into powder, and obtain the feed for compression molding.

[0141] 3. The powdered feed material for compression molding obtained in step 2 is screened, and the obtained powdered feed material D50 is 0.1-0.3 mm. The molding process parameters include:

[0142] Molding temperature: 150℃

[0143] Molding pressure: 70MPa

[0144] Molding insulation time: 10min

[0145] 4. Degrease the sample formed in step 4 with nitric acid to obtain a degreased blank. The nitric acid degreasing process parameters include:

[0146] Nitric acid intake: 4g / min

[0147] Degreasing temperature: 120℃

[0148] Degreasing time: 5h

[0149] 5. The sample after degreasing in step 4 is subjected to atmospheric pressure sintering to obtain the product. The atmospheric pressure sintering process parameters include:

[0150] Sintering temperature: 1500℃

[0151] Sintering holding time: 2h

[0152] Sintering rate: 5℃ / min

[0153] Example 4

[0154] The feeding formula is:

[0155] High-density polyethylene: 0.30kg

[0156] Ethylene-vinyl acetate copolymer: 0.20kg

[0157] Stearic acid: 0.20kg

[0158] Paraffin: 0.25kg

[0159] Polyoxymethylene: 1.23kg

[0160] Ceramic powder: 0.88kg

[0161] The ceramic powder is selected according to the formula of the present invention, the same below.

[0162] Processing method:

[0163] 1. Heat the internal mixer to the set temperature of 120℃, add ceramic powder and slowly stir and dry for 15 minutes.

[0164] 2. Add the mixed adhesive into an internal mixer and mix it with the ceramic powder. The temperature of the internal mixer is 190°C, the speed of the internal mixer is 18 r / min, and the total mixing time is 2.5 hours. Stir until it becomes a dough. Lower the temperature of the internal mixer to 90°C, continue to stir the dough-like mixture formed in step 2, the speed of the internal mixer is 13 r / min, the mixing time is 15 minutes, crush it into powder, and obtain the feed for compression molding.

[0165] 3. The powdered feed material for compression molding obtained in step 2 is screened, and the obtained powdered feed material D50 is 0.1-0.3 mm. The molding process parameters include:

[0166] Molding temperature: 150℃

[0167] Molding pressure: 70MPa

[0168] Molding insulation time: 10min

[0169] 4. Degrease the sample formed in step 4 with nitric acid to obtain a degreased blank. The nitric acid degreasing process parameters include:

[0170] Nitric acid intake: 4g / min

[0171] Degreasing temperature: 120℃

[0172] Degreasing time: 5h

[0173] 5. The sample after degreasing in step 4 is subjected to atmospheric pressure sintering to obtain the product. The atmospheric pressure sintering process parameters include:

[0174] Sintering temperature: 1500℃

[0175] Sintering holding time: 2h

[0176] Sintering rate: 5℃ / min

[0177] Comparative Example

[0178] Conventional ceramic feedstock is used, and the molding, debinding and sintering processes adopt the same processing methods as the above examples.

[0179] The product performance parameters were tested by making standard parts of the feed materials of each example by a compression molding process. The performance of the products made by the ceramic feed materials of the embodiments of the present invention and the products made by the comparative examples are shown in Table 1 below. On the basis of maintaining high density, high hardness and excellent bending strength of the products, the feed materials for ceramic compression molding and the molding method thereof provided by the present invention can make the production efficiency higher.

[0180] Performance Data <![CDATA[Density g / cm 3 > Linear shrinkage (%) Hardness HV Bending strength MPa Example 1 6.05 22.41 1384.53 1073.25 Example 2 6.01 22.33 1352.25 1068.37 Example 3 5.98 22.29 1332.50 1053.45 Example 4 6.03 22.37 1348.53 1065.49 Comparative Example 5.94 21.5 1225.41 904.12

[0181] The implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A feed material for ceramic compression molding, characterized in that: It comprises ceramic powder and adhesive, wherein the mass ratio of the ceramic powder to the adhesive is (1.5-2):(8.5-8); The ceramic powder includes the following components in percentage by mass: Zirconia: 92.5~96.5% Yttrium oxide: 3-6% Alumina: 0.1-1%; The adhesive comprises the following components in percentage by mass: High-density polyethylene: 8-13% Ethylene-vinyl acetate copolymer: 4-7% Stearic acid: 3-8% Paraffin: 8-18% Polyoxymethylene: 60-70%.

2. A feed material for ceramic compression molding according to claim 1, characterized in that: The volume density of the ceramic powder is 1.3-1.4 g / ml.

3. A feed material for ceramic compression molding according to claim 1, characterized in that: The particle size D50 of the ceramic powder is 400-500 nm.

4. A ceramic molding feed material and molding method according to claim 1, characterized in that: The feed material needs to be obtained through drying and mixing. The drying mainly includes: Heat the internal mixer to the set temperature, add the ceramic powder, slowly stir and dry. The drying temperature of the ceramic powder is 120±10℃, and the drying time is 10 to 20 minutes.

5. A method for forming a feed material for ceramic compression molding according to any one of claims 1 to 4, characterized in that: The feed material is obtained by drying and mixing; The banburying mainly includes: Add the mixed adhesive into an internal mixer and mix it with the ceramic powder. The temperature of the internal mixer is 170-200°C, the speed of the internal mixer is 5-30r / min, the total mixing time is 2-3h, and the mixture is stirred until it becomes dough-like. Lower the temperature of the internal mixer to 80-100°C, the speed of the internal mixer is 5-30r / min, and the mixing time is 10-30min to obtain a powdered feed for compression molding.

6. A method for forming a feed material for ceramic compression molding according to claim 5, characterized in that: The powdery feed material for compression molding is screened to obtain a powdery feed material with a D50 of 0.1 to 0.3 mm, and then compression molding is performed to obtain a green body.

7. A method for forming a feed material for ceramic compression molding according to claim 6, characterized in that: The molding process parameters include: molding temperature: 120-180°C; molding pressure: 40-100MPa; molding insulation time: 5-20min.

8. A method for forming a feed material for ceramic compression molding according to claim 6, characterized in that: The compression molded green body is degreased to obtain a degreased green body, which is then sintered to obtain the ceramic product.

9. A method for forming a feed material for ceramic compression molding according to claim 8, characterized in that: The degreasing adopts a nitric acid degreasing process, and the degreasing parameters include: nitric acid feed amount: 3-5 g / min; degreasing temperature: 110-130° C.; degreasing time: 3-5 h.

10. A method for forming a feed material for ceramic compression molding according to claim 8, characterized in that: The sintering adopts normal pressure sintering, and the process parameters include: sintering temperature: 1400-1600° C.; sintering heat preservation time: 2-4 hours; sintering rate: 2-5° C. / min.